Kompetensi Aparatur dan Budaya Organisasi: Kunci Peningkatan Kinerja di Inspektorat Jenderal Kementerian Pertanian - Hidayat, Rahmat (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2024)
There is a mismatch between expectations and reality in organizational culture that results in low employee and overall organizational performance. An in-depth study is needed to resolve organizational performance issues. This study aims to analyze the impact of apparatus competence and organizational culture on the performance of the Inspectorate General of the Ministry of Agriculture. In a quantitative approach with an associative method, the independent variables are apparatus competence (X1) and organizational culture (X2), while the dependent variable is organizational performance (Y). By understanding the correlation between these aspects, this study is expected to provide strategic contributions to development and management policies at the organizational level.